Pengaruh Edukasi Pengelolaan Sampah Plastik 3R Terhadap Pengetahuan Ibu Di Desa Helvetia Kecamatan Labuhan Deli Kabupaten Deli Serdang Tahun 2020 - Damanik, Yunita Syahputri; Ginting, Rian Fedriko; Simbolon, Esrinawati (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2021)
The Pollution caused by plastic increasingly worrying if there is no attempt to resolve it. Lack of knowledge in management can cause health problems, Destroying the aesthetic value of the environment, flooding, and increasing disease vectors. Judging from the problems above, education is needed on 3R Plastic waste management, especially for housewives..The purpose of this study to determine the effect of 3R plastic waste management education on knowledge of housewives. The study was conducted in Helvetia Village, Labuhan Deli Deli Serdang. The analytic study survey with Quasi Experimental study ,the Sample was 70 respondents with simple random sampling. The Research tool used questionnaires and education using posters. The Analyzed used univariate and bivariate analysis with statistical test Wilcoxson. Statistical results showed the value of p = 0.00 <0.05. That shows less than 0.05 then Ha is accepted. There was a significant effect between the 3R plastic waste management education on housewife's knowledge in Helvetia Village, Labuhan Deli, Deli Serdang in 2020.To the local government in Helvetia Village and their staff to promote education on independent plastic waste management to reduce the amount of plastic waste being disposed of making an application program for the use of plastic waste to become items of economic value.